DID COACHING, TRAINING AND DEVELOPMENT, EMPOWERMENT AND PARTICIPATION ON SCHOOL EMPLOYEES PERFORMANCE? - Purwanto, Agus; Prasetya, Agustian Budi (Journal of Industrial Engineering & Management Research, 2021)
The purpose of this study was to analyze the relationship between coaching and employee performance, to analyze the relationship between training and development on employee performance, to analyze the relationship between empowerment and employee performance and to analyze the relationship between participation and employee performance. This research method is a quantitative method and the method for data processing is by using PLS and using the SmartPLS version 3.0 software. Data Collection by distributing online questionnaires to 120 schools employees from all fields who meet these requirements and the results of research, the questionnaire returned as many as 90 questionnaires. Based on the results of data analysis, it is concluded that the coaching variable has a significant effect on employee performance. An increase in coaching variables will be followed by an increase in employee performance and a decrease in the coaching variable will be followed by a decrease in employee performance. Training and development has effect on employee performance. The increase in the. The training and development variable will increase the training and development variable and the decrease in the training and development variable will decrease the employee performance variable.